JARINGAN TERORIS SOLO DAN IMPLIKASINYA TERHADAP KEAMANAN WILAYAH SERTA STRATEGI PENANGGULANGANNYA (Studi Di Wilayah Solo, Jawa Tengah) - Fajar Purwawidada (Jurnal Ketahanan Nasional, 2014)
The Solo terrorism network was affected by the Darul Islam which had mutated into radical Islam groups and then into new terrorist group. The main reason was new political motive with religious cover and supported with other factors. The purpose of this research was to discovered the origin, extend, and cause of the terrorism establishment and to discover the Indonesia’s terrorism. The object of this research was Solo terrorism network as the biggest terrorist network in Indonesia with connection to various countries, and also all Indonesia terrorism related to this network. This research was conducted with in depth interview on the terrorist victims, agency, and former sect member who considered as terrorist. It showed that the Solo new group network was more amateur than the older one even though the ideology was similar. The Solo terrorism actions had affected the regional security especially the ideology, politics, economic, social and human security. Terrorism prevention in Solo had caught and dismantle Solo new terrorism network although with various flaws that needed to be fixed. The effective terrorism prevention strategies were law enforcement, prevention, deradicalization, and disengagement which had to well organized and shared together.Keywords: Solo Terrorist Network, Regional Security, Prevention Strategy